Religio as central element of the Roman identity in Cicero's De divinatione - Cairo, María Emilia (Quaderni Urbinati di Cultura Classica.)
In this paper we propose a reading of De divinatione in which every aspect of religio, i. e. rituals, priest colleges, the ways to communicate with the gods is presented not only for descriptive reasons (as it is usually understood), but also as a means of defining Romans as a unique people and of distinguishing them from others. We examine the ways in which the religious component takes part in the formulation of what Cicero understands as Roman. Our presentation is organized in two sections. In the first one, we analyse the contrast between Romans and others -- i. e., how Roman divinatory practices are contrasted with foreign ones when it comes to the definition of Romanness. In the second section, we study the definition of this "Wir-Identität" (as Assmann 2000 defines it) considering Cicero's presentation of the Roman religious system as a model of pietas.